RESPONS PEMBERIAN BERBAGAI DOSIS MOL DAUN KELOR DENGAN PENAMBAHAN KULIT BUAH PISANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS - Kurniawan Dj Laepo; Aris Aksarah Pas; Idris Idris (Jurnal Agrotech, 2019)
This study aims to study and determine the effect of various doses of Moringa leaf Mole by adding banana peels to the growth and yield of sweet corn plants (Zea mays saccharata Sturt.) Because they see that the development of environmentally friendly agriculture is a must for the continuity of production and health. These efforts have been recommended by the government, one of the efforts made is to conduct an organic farming business. This research was carried out in the Kalukubula Sub-District, Dolo District, Sigi Regency, Central Sulawesi Province. This study used a one-factor randomized block design (RBD), grouping was done based on the direction of the arrival of sunlight by treating various doses of MOL Moringa leaves with the addition of banana peels. The treatment tried consisted of 4 levels, namely: PM0: No MOL (Control), PM1: 200 ml + 2 liters of water / plot, PM2: 400 ml + 2 liters of water / plot, PM3: 600 ml + 2 liters of water / plot . Each treatment that was tried was repeated three (3) times, then there were 3 x 4 = 12 experimental units. To determine the effect of the treatment that was tried on plants, a variety of analyzes and treatments were carried out which significantly affected followed by a BNJ test α = 0.05. The results showed that the response of various doses of mole dun moringa with the addition of banana peels to the growth and yield of sweet corn on observing the number of leaves, stem circumference, mixed age, ear length, ear circumference, ear weight (g), ear weight per plot ( kg) and weight of ear per hectare (t) did not have a significant effect, while the treatment of Moringa leaf Mole with the addition of banana peels at a dose of 600 ml + 200 liters of water (PM3) significantly affected plant height at 15, 30 and 45 HST (28 , 70, 52.15 and 96.28) and the length of leaves at the ages of 15, 30 and 45 HST (20,14, 41,07 and 67,32) in sweet corn plants.